Ultrasonic-assisted hydrogen peroxide leaching of cadmium-containing flue dust under room temperature and neutral conditions: Efficient recovery and mechanism - Yuxi Xie; Tian Wang; Yuanru Wang; Yan Gao; Shihao Liu; Fei Niu; Phan Duc Lenh; Thiquynhxuan Le; Libo Zhang (Ultrasonics Sonochemistry)
A novel ultrasonic-enhanced hydrogen peroxide leaching method is proposed for efficient cadmium recovery from flue dust under room temperature and neutral conditions, addressing the limitations of conventional methods such as low efficiency and environmental pollution. Under optimal conditions (room temperature, 5 mL H2O2, 2:1 liquid–solid ratio, 20 min, and 360 W ultrasonic power), the cadmium leaching efficiency reaches 96.76 %, significantly higher than the conventional oxidative leaching efficiency of 88.57 %. Mechanistic studies indicate that ultrasound inhibits particle agglomeration, disrupts encapsulated structures, and generates hydroxyl radicals, enhancing oxidation of cadmium and lead-containing phases for efficient separation. Kinetic studies reveal that the introduction of ultrasound reduces the activation energy from 16.198 to 3.389 kJ·mol−1, changing the rate-determining step from a mixed control to diffusion control, thereby accelerating leaching kinetics. This method not only enhances cadmium recovery but also reduces environmental impact, offering a greener and more efficient solution for the lead smelting industry.